Characterization of two novel intronic OPA1 mutations resulting in aberrant pre-mRNA splicing - Bolognini, Ramona; Gerth-Kahlert, Christina; Abegg, Mathias; Bartholdi, Deborah; Mathis, Nicolas; Sturm, Veit; Gallati, Sabina; Schaller, André (BMC medical genetics, 2017)
Background We report two novel splice region mutations in OPA1 in two unrelated families presenting with autosomal-dominant optic atrophy type 1 (ADOA1) (ADOA or Kjer type optic atrophy). Mutations in OPA1 encoding a mitochondrial inner membrane protein are a major cause of ADOA. Methods We analyzed two unrelated families including four affected individuals clinically suspicious of ADOA. Standard ocular examinations were performed in affected individuals of both families. All coding exons, as well as exon-intron boundaries of the OPA1 gene were sequenced. In addition, multiplex ligation-dependent probe amplification (MLPA) was performed to uncover copy number variations in OPA1 . mRNA processing was monitored using RT-PCR and subsequent cDNA analysis. Results We report two novel splice region mutations in OPA1 in two unrelated individuals and their affected relatives, which were previously not described in the literature. In one family the heterozygous insertion and deletion c.[611-37_611-38insACTGGAGAATGTAAAGGGCTTT;611-6_611-16delCATATTTATCT] was found in all investigated family members leading to the activation of an intronic cryptic splice site. In the second family sequencing of OPA1 disclosed a de novo heterozygous deletion c.2012+4_2012+7delAGTA resulting in exon 18 and 19 skipping, which was not detected in healthy family members. Conclusion We identified two novel intronic mutations in OPA1 affecting the correct OPA1 pre-mRNA splicing, which was confirmed by OPA1 cDNA analysis. This study shows the importance of transcript analysis to determine the consequences of unclear intronic mutations in OPA1 in proximity to the intron-exon boundaries.